Rabconnectin3α Promotes Stable Activity of the H(+) Pump on Synaptic Vesicles in Hair Cells - Einhorn, Zev (Society for Neuroscience, 2012)
Acidification of synaptic vesicles relies on the vacuolar-type ATPase (V-ATPase) and provides the electrochemical driving force for neurotransmitter exchange. The regulatory mechanisms that ensure assembly of the V-ATPase holoenzyme on synaptic vesicles are unknown. Rabconnectin3α (Rbc3α) is a potential candidate for regulation of V-ATPase activity because of its association with synaptic vesicles and its requirement for acidification of intracellular compartments. Here, we provide the first evidence for a role of Rbc3α in synaptic vesicle acidification and neurotransmission. In this study, we characterized mutant alleles of rbc3α isolated from a large-scale screen for zebrafish with auditory/vestibular defects. We show that Rbc3α is localized to basal regions of hair cells in which synaptic vesicles are present. To determine whether Rbc3α regulates V-ATPase activity, we examined the acidification of synaptic vesicles and localization of the V-ATPase in hair cells. In contrast to wild-type hair cells, we observed that synaptic vesicles had elevated pH, and a cytosolic subunit of the V-ATPase was no longer enriched in synaptic regions of mutant hair cells. As a consequence of defective acidification of synaptic vesicles, afferent neurons in rbc3α mutants had reduced firing rates and reduced accuracy of phase-locked action potentials in response to mechanical stimulation of hair cells. Collectively, our data suggest that Rbc3α modulates synaptic transmission in hair cells by promoting V-ATPase activity in synaptic vesicles.